Development of a Real-Time Reverse Transcription Polymerase Chain Reaction Assay for Una Virus - Sara Ping; Jesse Waggoner (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Una virus (UNAV) is an understudied alphavirus with the capacity to infect humans. Although it was discovered decades ago in South America, little is still known about this virus because accurate diagnostic tests are still needed. The first UNAV-specific real-time reverse transcription polymerase chain reaction (rRT-PCR) test is described in the present study. This assay targets the nonstructural protein 1 coding region and was designed from an alignment using all available UNAV sequences. The linear range of the UNAV rRT-PCR extended from 6.2 to 0.2 log 10 copies/ µ L, with a lower limit of 95% detection of 2.0 copies/ µ L. The assay offered sensitive UNAV detection in contrived whole-blood samples. In addition, no amplification was observed in the assay when tested with genomic RNA from multiple closely related arboviruses. The UNAV rRT-PCR exhibits high sensitivity and specificity, which is critical for research into this virus in regions where multiple related alphaviruses co-circulate.